TELAAH KONFLIK DALAM NOVEL REMBULAN TENGGELAM DI WAJAHMU KARYA TERE LIYE - Refni Yunita (Universitas Bengkulu, 2016)
The aim of this study was to describe the internal conflict in the novel Rembulan Tenggelam di Wajahmu by Tere Liye. The study adapted the descriptive research design. The approach used in this study was literature psychology. The data were in the form of texts. The source of the data used in this study was the novel of Rembulan Tenggelam di Wajahmu. The data were collected by reading, comprehending, and note-taking. It was then analyzed by data reduction, data categorization, drawing conclusion and writing report. The result of this study shows that there are two factors that cause the internal conflict of main character (Rehan), they were: personal factor and situational factor. Personal factor consists of biological and socio-psychological factors. While the situational factor consists of ecology factor, design and architecture factor, condition-behavior factor, and psychosocial factor. As the result of the internal conflict experienced by Rehan are frustration, disappointment, agony, and anger. While the mechanism of ego-defense exercised by Rehan are repression, denial, reaction formation, movement, rationalization, and regression.